2010
DOI: 10.1111/j.1365-2141.2010.08318.x
|View full text |Cite
|
Sign up to set email alerts
|

research paper: IL1RN VNTR and IL2−330 polymorphic genes are independently associated with chronic immune thrombocytopenia

Abstract: Summary Chronic Immune Thrombocytopenia (cITP) is an acquired immune‐mediated disease associated with a T‐helper cell type 1 (Th1) immune polarization, whose genetic risk factors, however, are largely unknown. We investigated polymorphisms in promoter regions of genes that code molecules involved in proinflammatory immune response [IL1B−31T/C, IL1RN variable number tandem repeats (VNTR), IL2−330T/G, and TNF−307G/A] as well as in genes that code Toll like receptors (TLR) (TLR2 Arg753Gln, TLR4 Asp299Gly and TLR5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
2
19
0
1
Order By: Relevance
“…Recently, our group evaluated the serum cytokine profile of 98 patients with chronic ITP (platelet less than 100 × 10 9 /L) [6] attending the University Hospital, Universidade Federal de Minas Gerais, Brazil and demonstrated higher levels of Th17 cell-related cytokines, in addition to Th1-associated cytokines in the patients than in blood donor controls. We have also demonstrated [7] that IL1RN VNTR and IL2- 330 allele polymorphisms were associated with increased concentrations of IL-1β and of IL-2, respectively and were risk factors for chronic ITP. In this study, we compared serum Th1 and Th17 cytokine profile of 28 individuals (13 female and 15 male, mean age 49.2 years, range from 19 to 79 years) with persistent borderline thrombocytopenia with that of chronic ITP patients and controls we have previously evaluated [6].…”
Section: To the Editormentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, our group evaluated the serum cytokine profile of 98 patients with chronic ITP (platelet less than 100 × 10 9 /L) [6] attending the University Hospital, Universidade Federal de Minas Gerais, Brazil and demonstrated higher levels of Th17 cell-related cytokines, in addition to Th1-associated cytokines in the patients than in blood donor controls. We have also demonstrated [7] that IL1RN VNTR and IL2- 330 allele polymorphisms were associated with increased concentrations of IL-1β and of IL-2, respectively and were risk factors for chronic ITP. In this study, we compared serum Th1 and Th17 cytokine profile of 28 individuals (13 female and 15 male, mean age 49.2 years, range from 19 to 79 years) with persistent borderline thrombocytopenia with that of chronic ITP patients and controls we have previously evaluated [6].…”
Section: To the Editormentioning
confidence: 88%
“…Also, the patients with ITP and individuals with platelet count between 100 and 150 × 10 9 /L did not differ in respect to the mean age (p = 0.32), gender (p = 0.20) and duration of thrombocytopenia (p = 0.82). Here we also reanalyzed the data of cytokine gene polymorphisms of 122 patients with platelet count bellow 150 × 10 9 /L published elsewhere [7] by stratifying the group into those with platelet count less than 100 × 10 9 /L and those with platelets between 100 and 150 × 10 9 /L. The presence of at least one allele 2 of IL1RN and one G polymorphic allele of IL2-330 was more frequently observed in the group of subjects with platelet count between 100 and 150 × 10 9 /L (p = 0.04 and p = 0.03, respectively) than in the controls, as well as in the patients with platelets less than 100 × 10 9 /L (p = 0.007 and p = 0.02, respectively) than in the controls, but they did not differ between the patient groups (p = 0.8 and p = 0.7 for IL1RN and IL2 polymorphisms, respectively).…”
Section: To the Editormentioning
confidence: 99%
“…Thus, conditions that are associated with increased Th1 cytokine production may play a part in the pathogenesis of the disease. In fact, in a previous study we demonstrated 22 that cITP is associated with polymorphisms in genes linked to Th1 cell response. Increased levels of IL-1b and of IL-2/INF-γ were observed in the carriers of the polymorphic alleles of IL1RN VNTR and IL2-330, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The etiology of ITP remains unclear, but both genetic and environmental factors are thought to play role in the development of the disease. Several genes involved in immune system regulation like cytokine genes [3,4,5,6], Fc gamma receptor genes [4,7], CTLA-4 gene [8,9], and HLA genes [10], as well as some infective agents like hepatitis C virus, HIV (Human Immunodeficiency Virus), and helicobacter pylori [11,12,13] have been associated with susceptibility to ITP in several studies.…”
Section: Introductionmentioning
confidence: 99%